Emerging pharmacological approaches for Huntington's disease - Singh, Kuldeep; Jain, Divya; Sethi, Pranshul; Gupta, Jeetendra Kumar; Tripathi, Arpan Kumar; Kumar, Shivendra; Sarker, Satyajit D; Nahar, Lutfun; Guru, Ajay (European journal of pharmacology, 2024)
Huntington's disease (HD) is a progressive neurodegenerative disorder characterized by cognitive, motor, and psychiatric symptoms. Despite significant advances in understanding the underlying molecular mechanisms of HD, there is currently no cure or disease-modifying treatment available. Emerging pharmacological approaches offer promising strategies to alleviate symptoms and slow down disease progression. This comprehensive review aims to provide a critical appraisal of the latest developments in pharmacological interventions for HD. The review begins by discussing the pathogenesis of HD, focusing on the role of mutant huntingtin protein, mitochondrial dysfunction, excitotoxicity, and neuro-inflammation. It then explores emerging therapeutic targets, including the modulation of protein homeostasis, mitochondrial function, neuro-inflammation, and neurotransmitter systems. Pharmacological agents targeting these pathways are discussed, including small molecules, gene-based therapies, and neuroprotective agents. In recent years, several clinical trials have been conducted to evaluate the safety and efficiency of novel compounds for HD. This review presents an update on the outcomes of these trials, highlighting promising results and challenges encountered. Additionally, it discusses the potential of repurposing existing drugs approved for other indications as a cost-effective approach for HD treatment. The review concludes by summarizing the current state of pharmacological approaches for HD and outlining future directions in drug development. The integration of multiple therapeutic strategies, personalized medicine approaches, and combination therapies are highlighted as potential avenues to maximize treatment effectiveness.
Keywords: Pharmacological approaches; Animals; Neuroprotective Agents; protein huntingtin; neuroprotektivní látky; Humans; genetická terapie; Huntingtonova nemoc; Mitochondria; Genetic Therapy; lidé; mitochondrie; Neurodegenerative disorders; zvířata; Mutant huntingtin protein; Huntingtin Protein; Huntington Disease; Mitochondrial dysfunction; Huntington's disease